A Study on Cash Flow Analysis in Sri Anantha Lakshmi Spinning Mills Pvt. Ltd., Boyapalem, Guntur District - Prudhvi Raj, K.; Naveen, P. (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
This research paper provides a comprehensive analysis of the cash flow position of Sri Anantha Lakshmi Spinning Mills Pvt. Ltd., Guntur over a five-year period from 2020 to 2024. Cash flow statements are a critical component in assessing a company’s financial health, as they reflect the actual movement of cash in and out of a business, irrespective of accounting profits. This study focuses on evaluating the cash inflows and outflows from operating, investing, and financing activities to determine the liquidity, solvency, and sustainability of the company’s operations. The research relies on secondary data obtained from the company’s internal financial records. Through detailed year-on-year analysis and the use of visual tools such as graphs, the study identifies trends, strengths, and potential risks in the management of cash resources. The findings show a consistent increase in cash flow from operating activities, indicating robust core operations, while investment patterns reveal the company’s long-term strategic goals. Financing activities fluctuate, reflecting the company’s dynamic approach to managing debt and equity financing. The paper concludes that Sri Anantha Lakshmi Spinning Mills Pvt. Ltd. has demonstrated a stable and improving cash flow structure that supports business expansion and financial resilience. The insights drawn from this analysis can assist the company’s management, investors, and stakeholders in making informed financial decisions. Recommendations are provided to enhance cash management strategies for continued growth and efficiency.